2009
DOI: 10.5474/geologija.2009.009
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of detailed geochemical study of mercury at the ancient ore roasting site P{enk (Idrija area, Slovenia)

Abstract: P{enk is one out of 21 localities of ancient roasting sites in the woods surrounding Idrija and one of the largest localities of roasting vessels fragments. The most abundant pottery remains are found in the central western part of the area, which is about 60 m long and up to 50 m wide and is supposed to be the location of the roasting process itself. Detailed soil sampling was performed on 210 x 180 m big area. 156 soil (0-15 cm and 15-30 cm) and humus samples were collected from 73 sampling points. 3 soil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…4), which were active in the 16th and 17th century. These localities are highly contaminated, they surpass all described localities in Idrija, because former roasting processes led to considerable losses of Hg (Gosar and Čar, 2006;Teršič, 2010aTeršič, , 2010bTersič et al, 2008;Teršič and Gosar, 2009). Despite these hot spots being spatially limited, we can attribute the increased Hg content in all three profiles in the upper Idrijca Valley to the influence of historical small ore processing in the woods around Idrija.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…4), which were active in the 16th and 17th century. These localities are highly contaminated, they surpass all described localities in Idrija, because former roasting processes led to considerable losses of Hg (Gosar and Čar, 2006;Teršič, 2010aTeršič, , 2010bTersič et al, 2008;Teršič and Gosar, 2009). Despite these hot spots being spatially limited, we can attribute the increased Hg content in all three profiles in the upper Idrijca Valley to the influence of historical small ore processing in the woods around Idrija.…”
Section: Resultsmentioning
confidence: 80%
“…The main disadvantage of past studies was the fact that all of them were focused on the study of the Hg contamination and its transformation downstream of main and dominant source of pollution -Idrija Hg mine and ore roasting plant. But known from the recent findings (Gosar and Čar, 2006;Teršič, 2010aTeršič, , 2010bTersič et al, 2008;Teršič and Gosar, 2009), many small-scale ore roasting places existed in 16th century, scattered across the hills around Idrija. The highly contaminated material from these historical roasting sites was thus eroded during the centuries and also significantly contributed to the Hg concentrations in the alluvial sediments.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The preliminary investigations of mercury contents in soils at old roasting site locations (Gosar and Č ar 2006;Teršič and Gosar 2009;Teršič et al 2008) revealed that mercury contents in soils at these sites are very high, surpassing all hitherto described localities at Idrija and surroundings. It was estimated that there are about 40 tons of mercury still present at these sites (Gosar and Č ar 2006).…”
Section: Investigations Of Historical Mercury-ore Roasting Sitesmentioning
confidence: 96%